(untitled) - Langan, John (Boston, 2003)
This first joint-publishing venture between McGraw-Hill and John Langan's Townsend Press is a guide book to the essential skills necessary for students to make the transition from high school to college
Keywords: College student orientation,Định hướng sinh viên đại học,Kỹ năng học,Study skills